KOMUNIKASI BISNIS DALAM PROSES NEGOSIASI PENJUAL JASA SOL SEPATU KELILING - Hanny Hafiar; Heru Ryanto; Priyo Subekti (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
At this time, the door to door cobblers on average complained of the existence of the decline in thelevel of sales services their offers. Therefore, they are pursuing a strategy in an effort to increaseprofits, through negotiations in the bidding process improvements and pricing services. Therefore,this paper aims to discuss further so that it can be known how business communication activitiesthat take place in the process of the negotiations conducted by the seller of the services of the doorto door cobblers in the area of Bandung and its surroundings. This research uses descriptivemethods through the techniques of data collection by means of interviews and observations. As forthe results of the research showed their efforts to obtain the maximum benefit is done in two ways,namely: repair service deals with how to replace a broken, giving the option to replace potentiallydefective, as well as add service. As for the pricing is done with consideration based on the type ofshoes and characteristics of the service buyers.